An Analysis on the Integration of Machine Learning and Advanced Imaging Technologies for Predicting the Liver Cancer - Kelagadi, Hemantaraj M; Kumar K, Amit; D, Anandan; Vishnu Raja, P.; Senthilkumar, G.; L, Natrayan (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
This research analyzed the accuracy of machine learning models in classifying liver cancer based on CT and MRI scans. A dataset consisting of 2334 images of benign and malignant liver diseases is used. The authors perform a complete preprocessing pipeline that includes normalization, noise reduction, contrasting, and artifact removal. Image feature extraction uses traditional techniques like summing or deep learning algorithms. CNN architecture is central for liver condition classification. Specific convolutional networks included VGG16, ResNet50, and MobileNet. All of the models manifested considerable accuracy. VGG16 performed the best mechanically with an accuracy of 89.2 percent. The confusion matrices help visualize the models' abilities for correctly diagnosing liver disease states, even though there were some mistakes. Overall, the research emphasizes the importance and potential of advanced imaging technology combined with machine learning methods in early detection and diagnosis of liver cancer. The results have profound implications for patient care patients because they hint at new methods and machinery capable of earlier detection of cancers. Thus, technologies like those used in this experiment highlight the great promise shown by higher-tech methods. These results hold broad implications for thus improving the treatment of liver diseases by greater medical knowledge and technology. These results will require more rigorous research to validate them and continue developing medical imaging technology for liver cancers.